Cesarean section in Suriname using robson classification: a two-year nationwide cross-sectional study on rates, risk factors and perinatal outcomes of cesarean section - Zita D. Prüst; Josephine A. I. Dupont; Safir Liesdek; Kitty W. M. Bloemenkamp; Thomas van den Akker; Kim J. C. Verschueren; Lachmi R. Kodan (BMC Pregnancy and Childbirth)
Abstract Background Optimizing CS performance is a global health priority, given the maternal and perinatal morbidity and mortality associated with both underuse and overuse. This study aims to (1) determine the facility-based CS rate in Suriname and explore which women are most likely to undergo a CS and (2) classify all CS by the WHO Robson classification and analyze the perinatal outcomes. Methods An observational, cross-sectional study in Suriname, using nationwide birth registry data that included all hospital births in 2020 and 2021 (≥ 27 weeks of gestation). We used multivariate logistic regression analysis to assess maternal and perinatal characteristics associated with CS. We described cesarean births according to the Robson-10 classification and used descriptive statistics to analyze CS frequencies and perinatal outcomes. Results We analyzed the 18,917 women who gave birth in Surinamese hospitals, with an overall 23.9% CS rate (n = 4522/18,917). The highest CS rates were seen among women with a previous CS (69.3%, aOR 16.2, 95% CI 14.4–18.2), BMI > 40 (47.0%, aOR 5.1, 95% CI 4.0–6.5), newborn with a birthweight from or above 4,000 g (37.3%, 2.2, 95% CI 1.6–3.0) and women giving birth at hospital IV (38.5%, aOR 1.8, 95% CI 1.6–2.0). Hindustani women were more likely to give birth by CS compared to Maroon women (aOR 1.6, 95% CI 1.4–2.0). The largest contribution to the overall CS rate was Robson group 5 (i.e. multiparous women with a previous CS and a singleton term pregnancy in cephalic presentation, 30.5%, n = 1,378). Robson group 2 and 4 (i.e. pre-labor CS, or CS after induction, among term women without previous CS and cephalic presentation) contributed to 21.8% (n = 985) of all CS performed. Robson group 1 and 3 (i.e. during spontaneous labor CS among term women without previous CS and cephalic presentation) accounted for 23.3% (n = 1,052) of all CS cases. Conclusion The facility-based CS rate in Suriname is 24%, with substantial intra-country and inter-hospital variations. These disparities underscore the need for targeted interventions addressing both overuse and underuse of CS. Preventative measures should prioritize promoting safe VBAC, increasing assisted vaginal birth, preventing first-time CS and ongoing monitoring of trends and regular case audits.